Public-Private-People Partnerships in Lao PDR Forestry Sector - World Bank Group (World Bank, Vientiane, 2021)
Successive national socio-economic development plans have identified the private sector as the main engine of growth and the government of Lao PDR (GoL) is committed to fostering a transition to a private-sector-led market economy. In line with that approach, the GoL has pursued an increased role of public-private-people partnerships (PPPPs). However, the GoL’s ambitions are challenged by: no approved PPPP policy; there are still gaps in legal and institutional frameworks; there is a lack of a dedicated funding mechanisms to fund project development costs; there is no formalized mechanism to provide GoL technical and financial support; the institutional capacity is weak; and protracted approval processes are required to the highest levels of Government. As a result, few PPPP projects have been developed and implemented by GoL agencies. This policy note therefore lays out a path to achieve the long-term objectives of the GoL and the detailed policy actions required to realize its vision for PPPPs.